2022
DOI: 10.1021/acs.energyfuels.2c01166
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Biofuels and Biofuel Blends for Biogenic Carbon Quantification with Liquid Scintillation Radiocarbon Direct Measurement

Abstract: Radiocarbon activity of fuels is a direct analog to the biogenic fraction of carbon in the fuel. The amount of radiocarbon in a fuel sample may be determined by liquid scintillation direct analysis if the sample is relatively transparent to ultraviolet light. However, many biofuels are colorful which adversely affects the counting efficiency of this technique and therefore the precision which the biofuel blend level may be determined. In such cases, decolorization may be an approach to improve measurement prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It was concluded that all of the methods lead to a qualification of the biogasoline as an advanced biofuel with a high potential for greenhouse gas (GHG) emission reduction. Lee et al 19 studied the effectiveness of several decolorization techniques for different fuel types because the color of fuel samples can lower the precision of the liquid scintillation counting direct measurement techniques. They concluded that, although a technique to degrade chromophores is preferred, because it would not remove carbon from the sample, none of the techniques that were tested were effective.…”
Section: ■ Determination Of "Green" Carbon In the Co-processing Productsmentioning
confidence: 99%
“…It was concluded that all of the methods lead to a qualification of the biogasoline as an advanced biofuel with a high potential for greenhouse gas (GHG) emission reduction. Lee et al 19 studied the effectiveness of several decolorization techniques for different fuel types because the color of fuel samples can lower the precision of the liquid scintillation counting direct measurement techniques. They concluded that, although a technique to degrade chromophores is preferred, because it would not remove carbon from the sample, none of the techniques that were tested were effective.…”
Section: ■ Determination Of "Green" Carbon In the Co-processing Productsmentioning
confidence: 99%
“…There are also research studies focused on enhancing accuracy and identifying sources of CO 2 contamination, , particularly pertaining to air CO 2 pollution caused by various pathways. In recent years, there has been a growing application of the 14 C method in determining the ratio of mixed utilization of biogenic and fossil fuel, including the determination of biomass-coal blending ratios, , the biogenic carbon content of biobased liquid blended fuel, , and the biogas-natural gas blending ratios …”
Section: Introductionmentioning
confidence: 99%